SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SEPEDA MENGGUNAKAN METODE PROMETHEE - Ivan Hintoro; David (PROGRESS, 2022)
Toko Sepeda Super Top is a shop that sells various kinds of bicycles in Sekadau Regency. Not a few consumers are confused in choosing a bicycle. Based on the survey, 59.3% of respondents stated that it is difficult to choose a new bicycle. To assist consumers in choosing a bicycle, we need a system that can support consumers in making decisions. This study utilizes a Decision Support System (DSS) to support Toko Sepeda Super Top consumers in choosing a bicycle that suits their needs. The DSS method used is the Promethee type I method with the criteria used in the form of brand, price, durability, design, weight, and accessories. The form of research used in this research is a case study with a software design method, namely the prototype method. The result of this research is a bicycle selection DSS software that can be accessed by two levels of users. Admin can process bicycle data by inputting, updating, and deleting data. Then ordinary users can use a decision support system with the Promethee method to assist in bicycle selection.